Evaluasi Indikator Kinerja Teknologi Informasi Informasi pada Anak Perusahaan BUMN Bidang Jasa Teknologi - Afandi, Khoirunnisa; Suryanendra, Adjie; Anwar, Khoirul (LPPM Universitas dr. Soebandi, 2023)
This research is motivated by the declining performance of human resources in technology service companies. Therefore, this study aims to evaluate the performance of information technology in technology service companies and generate recommendations that can be used for company evaluations. We propose the integration of the SWOT-PESTLE method, which excels in analyzing the internal and external aspects of the company, with the Technology Readiness Index (TRI) method to measure the performance of information technology readiness in the organization based on surveys from its employees. As a result, we found that in the aspect of business applications, infrastructure, and information system processes, they have a significant impact on the decline in human resource performance, and therefore, this needs to be addressed to enhance human resource performance.